The Role of National Health Insurance in Achieving Universal Health Coverage: A Bibliometric and Systematic Perspective from African Countries - Gani, Professor Shenaaz (Journal of Ecohumanism, 2025)
This study investigates the scholarly landscape on National Health Insurance and its role in achieving Universal Health Coverage across African countries. Using a mixed-method approach that combines a bibliometric and systematic literature review (SLR), this paper synthesises insights from 78 peer-reviewed articles indexed in Scopus between 2011 and 2024. The aim is to map the intellectual, theoretical, and methodological contours of existing research while identifying regional disparities, conceptual ambiguities, and policy incoherencies. The findings revealed an uneven distribution of research, with South Africa, Ghana, and Nigeria dominating the discourse. A significant share of studies focusses on macro-level policy evaluations, with limited attention paid to implementation challenges, local-level perspectives, and non-state actors. Stakeholder and institutional theories underpin much of the literature, yet few studies advance new theoretical models tailored to Africa’s unique health governance contexts. Methodologically, the field remains heavily reliant on secondary data, with qualitative, longitudinal, and participatory approaches underutilized. The originality of this study lies in its comprehensive, structured analysis of the NHI–UHC nexus in Africa, offering a roadmap for researchers, practitioners, and policymakers to navigate the complex terrain of health financing and equity. Twenty research gaps are identified, offering firm ground for theoretical innovation, methodological pluralism, and context-sensitive policy research.